Maqsud Shaykhzoda left an indelible mark on the history of Uzbek literature with his work. (International conference on multidisciplinary science, 2025)
Maqsud Shaykhzoda has translated many unique works of world literature into Uzbek. Through his translations, Uzbek readers were able to get acquainted with the work of World Classics. Maqsud Shaykhzoda left an indelible mark on the history of Uzbek literature with his work. His works are still being studied in the literary environment and are guiding readers to ideas of love for the motherland, loyalty to the nation and humanism. His legacy remains a source of inspiration for the new generation